Предмет: Алгебра,
автор: Mikhail193
Упростите выражение (2x−3)^2−(2x−3)(2x+3)
Ответы
Автор ответа:
0
18-12x
(2x-3)^2-(2x-3)(2x+3)=
Квадрат разности и разность квадратов используем мы :D
=4х^2-12x+9-4x2+9=18-12x
(2x-3)^2-(2x-3)(2x+3)=
Квадрат разности и разность квадратов используем мы :D
=4х^2-12x+9-4x2+9=18-12x
Автор ответа:
0
Я уже решил, сначала не понял:D
Автор ответа:
0
Но спасибо за быструю реакцию
Похожие вопросы
Предмет: Физика,
автор: katyaantonuk3010
Предмет: География,
автор: aosrasd
Предмет: Биология,
автор: Diana2453
Предмет: Математика,
автор: mishana45347
Предмет: Геометрия,
автор: mahmud931993